2011
DOI: 10.1152/ajpcell.00374.2010
|View full text |Cite
|
Sign up to set email alerts
|

Placenta growth factor expression is regulated by hydrogen peroxide in vascular smooth muscle cells

Abstract: When supply arteries become occluded, blood is diverted through preexisting collateral vessels. Shear stress arising from this increase in blood flow provides the initial physiological stimulus for expansion of the collateral circulation, a process termed arteriogenesis. Endothelial cells (EC) respond to increased shear stress by releasing a variety of mediators that can act on underlying smooth muscle cells (SMC). Placenta growth factor (PLGF) is known to mediate certain aspects of arteriogenesis, such as rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…PLGF mRNA was increased in EC immediately after exposure to shear stress, whereas the increase in PLGF protein levels became detectable 8 h after exposure to shear stress. This time course is similar to the time course we previously reported for PLGF upregulation by H 2 O 2 in SMC (48). We also previously showed that PLGF protein levels can be regulated independently of PLGF mRNA levels (47).…”
Section: Discussionsupporting
confidence: 90%
“…PLGF mRNA was increased in EC immediately after exposure to shear stress, whereas the increase in PLGF protein levels became detectable 8 h after exposure to shear stress. This time course is similar to the time course we previously reported for PLGF upregulation by H 2 O 2 in SMC (48). We also previously showed that PLGF protein levels can be regulated independently of PLGF mRNA levels (47).…”
Section: Discussionsupporting
confidence: 90%
“…We further hypothesized that regulation of PLGF expression in SMC would be endothelium-dependent, since the shear signal is sensed by endothelium as discussed above. In agreement with this hypothesis, we previously reported that physiological levels of hydrogen peroxide (H 2 O 2 ) are released from EC in response to shear stress, and that H 2 O 2 can act as a paracrine mediator to increase PLGF gene and protein expression in vascular SMC (13). H 2 O 2 has received increasing attention as an important physiological signaling molecule in vascular biology.…”
Section: Introductionmentioning
confidence: 52%
“…Since inhibition of SOD causes decreased H2O2 levels in addition to increased O2 − , another interpretation of these results is that H2O2 is the ROS species required for arteriogenesis. In agreement with this hypothesis, Shaw et al recently demonstrated that the arteriogenic mediator placenta growth factor (PLGF) is upregulated by H2O2 in vascular smooth muscle cells (838). The role of H2O2 in vascular physiology has been recently reviewed (32, 783).…”
Section: Training Adaptations Within the Active Muscle: Increasedmentioning
confidence: 72%